FACTORS SHAPING THE IDENTITY OF THE MODERN CHINESE (Journal of Oriental Studies, 2019)
This article examines several major factors that influence the formation of the national identity of the Middle Kingdom inhabitants in the context of nowadays. The features of education, the Chinese national cuisine, the Chinese language, and the most important features of the existence and transformation of the principles of the Confucius teachings in modern conditions are revealed. At the same time, the influence of such important elements of globalization as new technologies and popular food products around the world was touched upon. By the example of the research, carried out in this work, the main reason and ways of preserving the Chinese national identity in the context of globalization were shown.Key words: China, Confucianism, national identity, factor, formation.